1997
DOI: 10.1002/art.1780400421
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in scleroderma among women in Michigan

Abstract: Objective. To examine racial differences in disease onset, extent, manifestations, and survival among women with scleroderma.Methods. A retrospective cohort study of women with scleroderma, diagnosed in Michigan between 1980 and 1991, was conducted. Clinical, laboratory, and demographic data were abstracted from the patients' medical records.Results. A total of 514 women with scleroderma were identified: 117 (23%) were black and 397 (77%) were white. Among black women, the mean age at diagnosis was lower (44.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
73
2
4

Year Published

1998
1998
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(89 citation statements)
references
References 23 publications
10
73
2
4
Order By: Relevance
“…No individual had documentation of the presence of both autoantibodies. ACA positivity was less common among black patients than among white patients (P Ͻ 0.001), as noted by other investigators (32,33), and was less common among male patients than among female patients (P Ͻ 0.001). As expected with this autoantibody pattern and as noted above, diffuse disease was more common in the black population compared with the non-black population.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…No individual had documentation of the presence of both autoantibodies. ACA positivity was less common among black patients than among white patients (P Ͻ 0.001), as noted by other investigators (32,33), and was less common among male patients than among female patients (P Ͻ 0.001). As expected with this autoantibody pattern and as noted above, diffuse disease was more common in the black population compared with the non-black population.…”
Section: Resultssupporting
confidence: 74%
“…As in other studies, ACAs were less frequent in black patients than in non-black patients (32,33). Of the 20 prevalent cases involving black men (5 of whom had limited disease), no individual had ACA positivity.…”
Section: Discussionsupporting
confidence: 79%
“…The b1ack:white ratio was 1.2:l except in young black women, for whom it was 10:1. Similar results were found in a population-based survey of the incidence of scleroderma in women in Michigan (104).…”
Section: Resultssupporting
confidence: 73%
“…Blacks are at higher risk compared with whites [2,4,10]. Laing et al [11] found a higher incidence among black women compared to white women (22.5 versus 12.8 per million per year respectively) and age at diagnosis was approximately 7 years younger among blacks.…”
mentioning
confidence: 95%